(untitled) (Research, Society and Development, 2023)
The study aimed to analyze “being a teacher today”, mapping the challenges of the profession, and presenting a contemporary reflection and historical on teaching practice in Brazilian Public Education. The research is methodologically structured as a bibliographical narrative with a qualitative approach. Data collection took place through the search platform "Google Academic", where the descriptors "Professor of the present" and "Professor and Educação Básica" were used. The searches and writing of the aforementioned article took place from January to July 2021. The analysis of the results followed the assumptions of Content Analysis. The results show that being a teaching professional, in contemporary society, is not an easy task since there are many factors that influence the professional teaching practice, from their training to professional constitution. In Brazil, from the 1990s onwards, studies and research on subjectivity and the social imaginary proliferated. These studies focus on the figure of the teacher as the center of the identification process of the teaching profession, revealing the myths, beliefs and representations that surround the pedagogical work in the classroom. During the mapping of the research, it is noted that there are several studies on teacher education, having as a starting point the personal characteristics and the professional life path of the teacher.